Kontribusi Minat Baca Sastra dan Penguasaan Konsep Cerpen terhadap Keterampilan Menulis Cerpen Siswa Kelas X SMK 1 Tanah Datar - Leli, Delfa; Saibi, Elvina A; Wahyuni, Uli (Jurnal Ilmiah Dikdaya, 2023)
Interest in reading literature reflects students' interest in literary works, including short stories, which can influence their motivation and dedication in understanding and producing literary works. Mastery of short story concepts refers to students' in-depth understanding of short story elements such as character, plot, setting, theme and language style. The aims of this research are: (1) the large contribution of interest in reading literature to students' short story writing skills, (2) the large contribution of mastery of short story concepts to students' short story writing skills, and (3) the large contribution of interest in reading literature and mastery of short story concepts to writing skills short story by class X students of SMK N 1 Tanah Datar. This research uses quantitative methods involving students from various levels of education. Data regarding interest in reading literature is measured through questionnaires and test results regarding mastery of short story concepts from short story analysis given to students. Next, short story writing skills are measured through a writing test. Data were analyzed using the Pearson Product Moment (PPM) correlation test, multiple correlation test, t test, F test, and the determinant coefficient formula to determine the contribution of the independent variable to the dependent variable, both individually and together. Research results shows that a high interest in reading literature contributes to better mastery of short story concepts. Students who have a high interest in reading literature tend to be more enthusiastic about short stories, identify short story elements better, and understand the concept and purpose of short story writing. Apart from that, good mastery of short story concepts also has a positive effect on students' short story writing skills. Students who have a strong understanding of the elements of short stories have a better ability to design interesting plots, develop in-depth characters, and compose short stories with good cohesion and coherence.